Agronomy improving the Fertility of Alluvial Soils in the Hazelnut Plantation Using Green Manures (Texas Journal of Agriculture and Biological Sciences, 2023)
The study refers to the selection of measures to increase the fertility of the alluvial soils of the georgian region - samegrelo in the hazelnut plantation, which is built in the training-trial farm of akaki tsereteli state university. the mentioned plantation was built as part of a scientific grant funded by the rustaveli national science foundation, at the base of the agricultural faculty of akaki tsereteli state university. the purpose of the research hazelnuts for the already existing industrial plantation, adapted to specific soil-climatic conditions, the selection of the best options for culture maintenance, which will be scientifically substantiated and supported by research. within the framework of the study, the determination of the level of soil fertility was carried out; the content of the main food elements - nitrogen, phosphorus and potassium in the forms available to the plant, the total amount of calcium and magnesium, humus content, actual acidity - PH. as part of our research, the focus is on the quality indicators of the nuts, which will ultimately lead to an increase in their price. so we decided to use in bio farms allowed fertilizers. try to include 4 options: I option-unfertilized (control) II option- fertilizer obtained from chicken manure ‘’biutera’’. III option- humic fertilizer ‘’geo humat’’; IV- option sideration, use of green fertilizers (sowing of tsertsvela). the paper presents soil research materials and the results obtained using one of the organic fertilizers used on the research site - siderate tsertsvela